Spark plasma reaction sintering of ZrO2-mullite composites from plasma spheroidized zircon/alumina powders - Yu, L. G. (2012)
Mullite-zirconia ceramic composites are prepared by reaction sintering of plasma spheroidized (PS) zircon-alumina powders in a spark plasma sintering (SPS) system at 1000, 1100, 1200 and 1300 °C with duration of 10 and 30 min. At SPS temperature of 1000 °C, evidence of zircon decomposition is detected, while at 1200 °C, mullite formation dominates the process, resulting in significant increases in microhardness, Young’s modulus and fracture toughness values. At SPS temperature of 1300 °C, due to recrystallization, rapid grain growth, and intergranular micro cracking, there is a slight decrease of microhardness and Young’s modulus values. Yet, fracture toughness as high as 11.2±1.1 MPa m1/2 is obtained by the indentation technique. The results indicate that with optimized sintering parameters, a combination of PS and SPS is effective in preparing high performance mullite/ZrO2 composites from zircon/alumina mixtures at a relatively low reaction sintering temperature.